Vaccine hesitancy and the reluctance to "tempt fate" - Ichino, Anna (Philosophical psychology, 2023)
This paper offers an explanation for subjects' lack of confidence in vaccines' safety, which in turn is widely recognized as one of the main determinants of vaccine hesitancy. I argue that among the psychological roots of this lack of confidence there is a kind of intuitive thinking that can be traced back to a specific superstitious belief: the belief that "it is bad luck to tempt fate". Under certain conditions, subjects perceive the choice to undergo vaccinations as an action that "tempts fate", and this leads them to overestimate its risks. When an action is perceived as "tempting fate", indeed, its possible negative outcomes are anticipated as highly aversive, and as such they capture subjects' imagination, thereby feeling more subjectively probable. This has important consequences for practical pro-vaccine interventions. Part of what makes an action perceived as "tempting fate" is its being free, arbitrary, and departing from one's typical behavior: insofar as vaccine hesitancy is driven by beliefs about tempting fate, then, we can predict the success of interventions that make vaccinations nearly mandatory, or build vaccination opportunities into health care routines as opt-out, rather than opt-in options, making them closer to something that subjects passively accept rather actively seek.